1997
DOI: 10.1097/00007691-199704000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Variability of Plasma Interferences on the Accuracy of Drug Immunoassays

Abstract: Most immunoassays applied to drugs in human plasma do not use an extraction of analyte. To compensate for interferences due to plasma proteins or salts, standards are prepared in drug-free plasma. Because the concentration of plasma components varies from one subject to another, it is likely that the drug-free plasma is not representative of the potential interference in each plasma. Using two immunoassays, for a steroid (nomegestrol acetate) and a heptapeptide (BN 52080), the authors have shown that tracer bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…It is known that the blank matrix used to construct standard curves in immunoassay may not reflect the variability in an individual matrix, which might lead to inaccuracy exceeding 30%. [16] A typical illustration appears from the comparative analysis of a fifth subject who was not included in the previous comparisons of EIA and LC/MS/MS. In this particular subject, AcSDPK-NH 2 immunoreactivity was detected by EIA before injection of the peptide, and the plasma concentrations measured by EIA during infusion were~10 times higher than those recorded for the other subjects ( Fig.…”
Section: Performances Of the Lc/ms/ms And Eia Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the blank matrix used to construct standard curves in immunoassay may not reflect the variability in an individual matrix, which might lead to inaccuracy exceeding 30%. [16] A typical illustration appears from the comparative analysis of a fifth subject who was not included in the previous comparisons of EIA and LC/MS/MS. In this particular subject, AcSDPK-NH 2 immunoreactivity was detected by EIA before injection of the peptide, and the plasma concentrations measured by EIA during infusion were~10 times higher than those recorded for the other subjects ( Fig.…”
Section: Performances Of the Lc/ms/ms And Eia Methodsmentioning
confidence: 99%
“…However, they may be plagued by poor specificity and interindividual matrix effects leading to reduced accuracy which may compromise the validation of candidate biomarkers for the diagnosis of disease states. [13][14][15][16] As an alternative to immunoassays, quantitative mass spectrometry (MS) has advantages in terms of robustness and specificity through the use of internal standards, adapted sample preparations and chromatographic separations. [13,[17][18][19] Mass spectrometry has already proved its applicability in the field of absolute quantitation of proteins and peptides in complex matrices such as plasma and urine, with sensitivity sometimes greater than that of enzyme immunoassay (EIA).…”
mentioning
confidence: 99%
“…Bilirubin (171 µmol/L) có thể ảnh hưởng tới định lượng acetaminophen và vancomycin. Lipid máu tạo ra độ đục gây chênh lệch kết quả đo phổ và sắc kí, vì vậy cần bị loại bỏ thông qua li tâm siêu tốc; protein niệu có thể ảnh hưởng tới sự gắn của chất phân tích với kháng thể trong quy trình định lượng miễn dịch [16,24,25].…”
Section: Một Số Vấn đề Trong Kĩ Thuật Thực Hiện Tdmunclassified
“…In this method absolute recovery was not reached, and the results indicated that differences of up to 32% between the reactivities of the antibodies to the gentamicin components existed [14]. Remarkable intersubject variability has been reported for immunoassays in general, and the accuracy of the results has been questioned, especially at low concentrations [15]. Isoherranen and Soback [12] developed a chromatographic method for reliable detection, identification, and quantification of three major gentamicin components in body fluids in the concentration range 0.1-20 mg/L.…”
Section: Introductionmentioning
confidence: 99%